Google Docs in English for Business Purposes courses: The exploration of students’ acceptance - Susilawati Susilawati; Yustika Nur Fajriah; Sri Yunita (ELT Forum: Journal of English Language Teaching, 2023)
serving as the foundation for reflection on learning, including in classes of EBP (English for Business Purposes) as a branch of ESP (English for Specific Purposes). The recent study aims at exploring EBP students’ acceptance of the use of Google Docs as a learning platform in their class using the framework of TAM (Technology Acceptance Model). A qualitative case study was adopted by administering an open-ended questionnaire and a structured-group interview. The participants involved were one class of EBP students consisting of 18 persons at one private university in Depok, West Java, Indonesia. The findings revealed that most of the students positively accept the use of Google Docs in their EBP writing class. Particularly, based on PU (Perceived Usefulness), the students viewed that Google Docs gives them assistance to write and improve their writing skills. In the view of PEU (Perceived Ease of Use), Google Docs has been seen as a user-friendly platform. The students also evinced a fine attitude in terms of ATT (Attitude Towards Technology). In the aspect of BI (Behavioral Intention), most students highlighted their preference for the use of Google Docs in the future, both for academic and professional purposes. Recommendations for ESP instructional practices with the utilization of Google Docs and potential research in the future are forwarded.